Who does Red Bull give wings to? Sensation seeking moderates sensitivity to subliminal advertisement - Bustin, Gaëlle M.; Jones, Daniel N.; Hansenne, Michel; Quoidbach, Jordi (Frontiers in Psychology, 2015)
This study assessed whether subliminal priming of a brand name of a drink can affect people’s choices for the primed brand, and whether this effect is moderated by personality traits. Participants with different levels of sensation seeking were presented subliminally with the words Red Bull or Lde Ublr. Results revealed that being exposed to Red Bull lead on average to small increases in participants’ preferences for the primed brand. However, this effect was twice as strong for participants high in sensation seeking and did not occur for participants low in sensation seeking. Going beyond previous research showing that situational factors (e.g., thirst, fatigue…) can increase people’s sensitivity to subliminal advertisement, our results suggest that some dispositional factors could have the same potentiating effect. These findings highlight the necessity of taking personality into account in non-conscious persuasion research.